Integrasi Kecerdasan Buatan dan Kecerdasan Emosional dalam Dialog Digital: Tinjauan Psikolinguistik terhadap Interaksi Generasi Modern - Fakhriyyah Asmay Aidha; Krismonika Khoirunnisa; Silfia Qurrotul A’yun (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study examines the evolving role of artificial intelligence (AI) in digital communication from a psycholinguistic and pragmatic perspective. Rather than functioning solely as a technical tool, AI has increasingly assumed the role of an interactive social entity capable of engaging in complex conversational exchanges. By simulating affective responses, employing politeness strategies, and adapting to users’ emotional and social contexts, AI fosters communication environments perceived as safe, particularly among the digital-native generations. These environments often relax rigid social norms such as fear of impoliteness or judgment, enabling deeper emotional expression. Employing a qualitative methodology grounded in literature review and observation of user interactions with Large Language Models (LLMs) based on platforms like ChatGPT. However, this research adopts a constructivist paradigm to examine how users co-construct meaning. Findings indicate that AI through technologies such as Natural Language Processing (NLP), affective computing, and relational artifact design facilitates perceptions of social presence, emotional alignment, and self-disclosure. This signifies a shift from traditional interpersonal communication to linguistically mediated digital interaction. However, the engagement remains a simulation for AI that lacks genuine intentionality or social consciousness and still struggles with implicit elements like metaphor or irony. The study concludes by advocating for interdisciplinary approaches to assess AI’s epistemic and affective roles in shaping social relationships and to critically reconsider concepts such as authenticity, artificial affect, and human subjectivity in the digital era.